(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2019)
A teaching-learning proposal is described for the treatment of optimization problems in the pre-university student. The theoretical-methodological elements fall into the heuristic principles and resources and the use of GeoGebra software, on this basis is conceived the identification, selection and formalization of the way of solution, control and assessment as fundamental stages. This work contributes to a proposal to approach the treatment of the study of the variation of the functions, prior to the classic presentation of the mathematical content using the derivative.